DYNAMIC PORTFOLIO UNDER DEFAULTY ASSETS - Amelda Rizal, Nora
This research aims to ?nd an optimal solution for dynamic portfolio in ?nite-time horizon under defaulty assets. Defaulty assets mean that the assets has a chance to be liquidated in a ?nite time horizon, e.g corporate bond. As a reference in making investment decisions, the concept of utility functions will play a role. Optimal portfolio composition will be obtained by maximizing the total expected discounted utility in the time span during the investment is executed.